Pengawasan Laboratorium Komputer di MAN 2 Palembang - Yanti, Rini Fitri; Niswah, , Choirun; Ibrahim, Ibrahim (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this research is to analyze the supervision of the computer laboratory at MAN 2 Palembang. In this study, the researcher used a qualitative approach with a descriptive type. The research informants included the Head of the Computer Laboratory, the Principal, and the Vice Principal for Facilities and Infrastructure. The data collection techniques used in data analysis were data reduction, data presentation, data verification, and conclusion drawing. The validity test of the research data employed source triangulation and technique triangulation. The results of this study indicate that the supervision of the computer laboratory at MAN 2 Palembang has been well implemented. The findings can be observed through the planning of computer laboratory supervision conducted by the principal in establishing the management of the computer laboratory organization, followed by the implementation of policies to ensure the efficient use of technology by setting rules and regulations for the computer laboratory, and finally, reporting and follow-up actions through routine inspections, problem documentation, and reporting to relevant parties regarding computer laboratory activities. The challenges in supervising the computer laboratory include a lack of awareness among users regarding the rules of the computer laboratory. Efforts to address these challenges include reprimanding teachers who do not directly supervise practical activities during the learning process, enforcing computer laboratory rules, using CCTV, and maintaining ongoing supervision.